Interoceptive accuracy is associated with emotional contagion in a valence- and sex-dependent manner. (3rd March 2020) - Lischke, Alexander; Weippert, Matthias; Mau-Moeller, Anett; Jacksteit, Robert; Pahnke, Rike
ABSTRACT: Over the last years, the neurobiological mechanisms of empathy have been extensively investigated. Recent investigations suggest that interoceptive processes, in particular, those that are related to the experience and perception of cardiac changes, are relevant for affect sharing, mentalizing and self-other distinction. To further investigate the association between interoception and affect-sharing, we measured emotional contagion and interoceptive accuracy in a sample of healthy participants ( n = 84). Emotional contagion was assessed with an established self-report questionnaire and interoceptive accuracy was assessed with a validated heartbeat detection task. Across a series of complementary analyses, we found a sex- and valence-dependent association between interoception and affection sharing: Among female but not male participants, interoceptive accuracy was positively associated with emotional contagion for negative but not positive states of others. We provide an evolutionary-based explanation for these findings, which are consistent with previous findings showing positive associations between interoceptive accuracy, mentalizing and self-other distinction.